APLIKASI ECOMMERCE BERBASIS BUSINESS to CONSUMER SEBAGAI PENJUALAN PRODUK MAKANAN RINGAN KHAS PRINGSEWU - Fauzi Fauzi; Adi Nurdian Candra; Kasmi Kasmi (Jurnal Signaling, 2019)
Electronic Commerce is an extension of e-commerce by exploiting electronic media. as electronic advances are increasingly advanced, it will force SMEs to evolve from manual to digital, this is because the existence of the internet as electronic media (e-commerce) has its own positive and negative impacts. The positive impact is the presence of the internet as a medium for selling marketing systems to become wider, simple and detailed. While the negative impact is when traditional business people will be displaced by the times due to lack of knowledge. The system to be built is a typical web-based sale of Pringsewu snacks, this website can display complete catalogs and catalogs with prices and types of food online also providing shopping process services. The result of designing this application is the development of applications from the sale of Pringsewu's specialty snacks online, buyers can easily find and see Pringsewu's specialty snacks and make it easier to carry out the process of buying and selling food.